Developing ICT curriculum in primary schools: processes, challenges, and solutions - Vina Salima Mujahida (Hipkin Journal of Educational Research, 2026)
The need for a curriculum that adapts to technological developments and student needs makes the Information and Communication Technology (ICT) curriculum a crucial part of elementary education, as it helps shape digital literacy from an early age. This study examines the process of ICT curriculum development at the elementary school level. The purpose of this study was to understand how the ICT curriculum was developed, who was involved in the process, and how it was implemented in the classroom. The research method used was a qualitative approach through interviews with school officials involved in curriculum development. The results showed that curriculum development was carried out by an internal school team and adapted to the school's conditions and needs. During the process, several obstacles were encountered, such as limited facilities and teachers' unequal understanding of ICT materials. Nevertheless, the school sought solutions by developing simple materials and implementing learning models that were enjoyable and easy for students to understand.   Abstrak Perlunya kurikulum yang adaptif terhadap perkembangan teknologi dan kebutuhan murid menjadikan kurikulum Teknologi Informasi dan Komunikasi (TIK) menjadi bagian penting dalam pendidikan dasar karena berperan dalam membentuk literasi digital sejak usia dini. Penelitian ini mengkaji proses pengembangan kurikulum TIK di tingkat sekolah dasar. Tujuan dari penelitian ini adalah untuk memahami bagaimana kurikulum TIK disusun, siapa saja yang terlibat dalam prosesnya, serta bagaimana penerapannya di kelas. Metode penelitian yang digunakan adalah pendekatan kualitatif melalui wawancara kepada pihak sekolah yang terlibat dalam pengembangan kurikulum. Hasil penelitian menunjukkan bahwa pengembangan kurikulum dilakukan oleh tim internal sekolah dan disesuaikan dengan kondisi serta kebutuhan sekolah. Dalam prosesnya, terdapat beberapa kendala seperti keterbatasan sarana dan belum meratanya pemahaman guru terhadap materi TIK. Meskipun demikian, sekolah berupaya mencari solusi melalui penyusunan materi yang sederhana dan penerapan model pembelajaran yang menyenangkan dan mudah dipahami oleh murid. Kata Kunci: kurikulum TIK; pembelajaran menyenangkan; sekolah dasar